PENERAPAN TEKNOLOGI PENGEMASAN PADA PENGOLAHAN TEPUNG SAGU KERING DI UKM “ENGKA SAGU AL-FURQAN” MAKASSAR SULAWESI SELATAN - Reta, .; Nurmiah, Siti; Zaimar, . (Jurnal Dinamika Pengabdian, 2020)
One of the productive potentials of sago is in the eastern part of South Sulawesi, namely in North Luwu and East Luwuk. Sago flour can be used widely as a substitute in the manufacture of other foods, such as noodles, bread, biscuits, cakes, flavoring foods, and various types of high fructose syrup drinks. Therefore, sago is a non-rice alternative commodity that is calculated to support the food diversification program launched by the Government. Considering high potential of sago, it is necessary to cultivate, process and market sago products and build a partnership between cultivation and processing / packaging SMEs of sago products. The problem with Engka Sagu SMEs is the limited production capacity to meet market demand with sufficient quantity and quality. The processing and packaging process is done manually so that the quality and capacity is very low, only around 360-500 kg per month. Meanwhile, the potential market demand could reach 2,500 kg (2.5 tons) per month. The problem-solving method used is the introduction and training of dry sago starch processing techniques and packaging to labeling. The results showed that the activities of counseling, training and mentoring on dry sago flour packaging techniques went well and according to the plan where the Engka Sagu SME was able to produce the dry sago flour properly. The packaging and labeling of the product can be done well and produce a product with an attractive identity and appearance and can be sold on line.   Keywords: Sago fluor, Engka Sagu SMEs, capacity, packaging.   ABSTRAK Potensi Sagu yang sudah produktif salah satunya adalah Sulawesi Selatan bagian Timur yakni di Luwu Utara dan Luwu Timur. Tepung sagu dapat digunakan secara luas sebagai  subsitusi dalam  pembuatan  makanan lain, seperti mie, roti, biskuit, kue, makanan penyedap, dan berbagai jenis minuman sirup berkadar  fruktosa  tinggi. Oleh karena itu, sagu  merupakan  komoditas  alternatif non beras yang diperhitungkan dalam  mendukung  program diversifikasi pangan yang dicanangkan oleh pemerintah. Melihat potensi Sagu yang sangat tinggi maka perlu usaha budidaya, pengolahan dan pemasaran produk Sagu dan kemitraan antara UKM budidaya dan UKM pengolahan/ pengemasan produk sagu tersebut. Permasalahan UKM Engka adalah keterbatasan kemampuan produksi untuk memenuhi permintaan pasar dengan jumlah dan kualitas yang tercukupi. Proses pengolahan dan pengemasan dilakukan secara manual sehingga kualitas dan kapasitasnya sangat kurang hanya sekitar  360-500 kg per bulan. Sedangkan potensi permintaan pasar  bisa mencapai 2.500 kg (2,5 Ton) per bulan. Metode pemecahan masalah yang digunakan berupa pengenalan dan pelatihan teknik pengolahan tepung sagu kering dan pengemasan sampai pada pelabelannya. Hasil yang didapatkan bahwa kegiatan penyuluhan, pelatihan serta pendampingan pada teknik pengemasan tepung sagu kering berjalan dengan baik dan sesuai rencana dimana UKM Engka Sagu sudah mampu memproduksi tepung sagu kering dengan baik. Pengemasan dan pelabelan pada produkpun sudah dapat dikerjakan dengan baik dan dihasilkan produk dengan identitas dan penampilan yang menarik serta sudah dapat dijual online buka lapak.   Kata Kunci; Tepung Sagu, UKM Engka Sagu, Kapasitas, Pengemasan.